Quantum tunneling and barrier hopping in MgTi2O5 nanoparticles: a study of AC/DC conductivity and dielectric response - Salwa, A. S.; Wasly, H. S.; Ioanid, Alexandra; Abd El-Sadek, M. S. (Frontiers in Physics, 2025)
The electrical conductivity and dielectric characteristics were investigated across a frequency range of 200–5 MHz and a temperature range of 318 K to 433K for MgTi2O5 nanoparticles (NPs). The electrical conductivity data displayed two dominant conduction mechanisms: a quantum mechanical tunneling model (QMT) and the correlated barrier hopping model (CBH). The activation energy values derived from the Direct Current (DC) Conductivity were 0.15 and 0.27 eV. In addition, the activation energy values derived from the Alternating Current (AC) Conductivity decreased as frequency increased from 0.13 to 0.014 eV due to the improvement of electronic jumps among localized states. Additionally, dielectric investigation of MgTi2O5 NPs within the frequency range from (200 – 5 MHz) and the temperature range from (318K–433K) revealed that both real (ε1) and imaginary (ε2) components of a dielectric permittivity decrease as the frequency increased and increased as a temperature increased due to thermal motion of electrons, which is related to the polarization mechanism.